Subunit-Dependent Surface Mobility and Localization of NMDA Receptors in Hippocampal Neurons Measured Using Nanobody Probes - Kortus, Stepan; Rehakova, Kristyna; Klima, Martin; Kolcheva, Marharyta; Ladislav, Marek; Langore, Emily; Barackova, Petra; Netolicky, Jakub; Misiachna, Anna; Hemelikova, Katarina; Humpolickova, Jana; Chalupska, Dominika; et al. (The Journal of neuroscience, 2023)
NMDA receptors (NMDARs) are ionotropic glutamate receptors that play a key role in excitatory neurotransmission. The number and subtype of surface NMDARs are regulated at several levels, including their externalization, internalization, and lateral diffusion between the synaptic and extrasynaptic regions. Here, we used novel anti-GFP (green fluorescent protein) nanobodies conjugated to either the smallest commercially available quantum dot 525 (QD525) or the several nanometer larger (and thus brighter) QD605 (referred to as nanoGFP-QD525 and nanoGFP-QD605, respectively). Targeting the yellow fluorescent protein-tagged GluN1 subunit in rat hippocampal neurons, we compared these two probes to a previously established larger probe, a rabbit anti-GFP IgG together with a secondary IgG conjugated to QD605 (referred to as antiGFP-QD605). The nanoGFP-based probes allowed faster lateral diffusion of the NMDARs, with several-fold increased median values of the diffusion coefficient (D). Using thresholded tdTomato-Homer1c signals to mark synaptic regions, we found that the nanoprobe-based D values sharply increased at distances over 100 nm from the synaptic edge, while D values for antiGFP-QD605 probe remained unchanged up to a 400 nm distance. Using the nanoGFP-QD605 probe in hippocampal neurons expressing the GFP-GluN2A, GFP-GluN2B, or GFP-GluN3A subunits, we detected subunit-dependent differences in the synaptic localization of NMDARs, D value, synaptic residence time, and synaptic-extrasynaptic exchange rate. Finally, we confirmed the applicability of the nanoGFP-QD605 probe to study differences in the distribution of synaptic NMDARs by comparing to data obtained with nanoGFPs conjugated to organic fluorophores, using universal point accumulation imaging in nanoscale topography and direct stochastic optical reconstruction microscopy.SIGNIFICANCE STATEMENT Our study systematically compared the localization and mobility of surface NMDARs containing GFP-GluN2A, GFP-GluN2B, or GFP-GluN3A subunits expressed in rodent hippocampal neurons, using anti-green fluorescent protein (GFP) nanobodies conjugated to the quantum dot 605 (nanoGFP-QD605), as well as nanoGFP probes conjugated with small organic fluorophores. Our comprehensive analysis showed that the method used to delineate the synaptic region plays an important role in the study of synaptic and extrasynaptic pools of NMDARs. In addition, we showed that the nanoGFP-QD605 probe has optimal parameters for studying the mobility of NMDARs because of its high localization accuracy comparable to direct stochastic optical reconstruction microscopy and longer scan time compared with universal point accumulation imaging in nanoscale topography. The developed approaches are readily applicable to the study of any GFP-labeled membrane receptors expressed in mammalian neurons.
Keywords: Neurons; live microscopy; mammalian neuron; receptory N-methyl-D-aspartátu; Rats; imunoglobulin G; synapse; GluN subunit; glutamate receptor; hipokampus; Receptors, N-Methyl-D-Aspartate; krysa rodu Rattus; Single-Domain Antibodies; jednodoménové protilátky; Immunoglobulin G; excitatory synapse; zvířata; Mammals; králíci; lateral diffusion; savci; Rabbits; neurony; Synapses; Hippocampus; Animals